Differential Effects of Temperature on Natural Transformation to Erythromycin and Nalidixic Acid Resistance in Campylobacter coli - Kim, Joo-Sung (American Society for Microbiology (ASM), 2008)
Campylobacter jejuni and Campylobacter coli are naturally competent, but limited information exists on the impact of environmental conditions on transformation. In this study, we investigated the impact of temperature and microaerobic versus aerobic atmosphere on transformation of C. coli to erythromycin and nalidixic acid resistance. Frequency of transformation was not significantly different between microaerobic (5 to 10% CO(2)) and aerobic conditions. However, C. coli was transformed to erythromycin resistance at a significantly higher frequency at 42°C than at 25°C (P < 0.05), and few or no transformants were obtained at 25°C. In contrast, transformation to nalidixic acid resistance was highly efficient at both 42°C and 25°C and was similar or, at the most, fourfold higher at 42°C than at 25°C. DNase I treatment experiments suggested that steps both prior and subsequent to internalization of DNA were influenced by temperature in the case of transformation of C. coli to erythromycin resistance. However, the moderately increased (fourfold) frequency of transformation to nalidixic acid resistance at 42°C compared to that at 25°C was exclusively associated with steps prior to DNA internalization. These findings suggest that transformation to erythromycin resistance may be significantly more frequent in the gastrointestinal tract of hosts such as poultry (at 42°C) than in other habitats characterized by lower temperatures, whereas transformation to nalidixic acid resistance may be highly efficient both within and outside the animal hosts.